Endothelial Basement Membrane Laminins as an Environmental Cue in Monocyte Differentiation to Macrophages - Lixia Li (Frontiers in Immunology, 2020)
Monocyte differentiation to macrophages is triggered by migration across the endothelial barrier, which is constituted by both endothelial cells and their underlying basement membrane. We address here the role of the endothelial basement membrane laminins (laminins 411 and 511) in this monocyte to macrophage switch. Chimeric mice carrying CX3CR1-GFP bone marrow were employed to track CCL2-induced monocyte extravasation in a cremaster muscle model using intravital microscopy, revealing faster extravasation in mice lacking endothelial laminin 511 (Tek-cre::Lama5−/−) and slower extravasation in mice lacking laminin 411 (Lama4−/−). CX3CR1-GFPlow extravasating monocytes were found to have a higher motility at laminin 511 low sites and to preferentially exit vessels at these sites. However, in vitro experiments reveal that this is not due to effects of laminin 511 on monocyte migration mode nor on the tightness of the endothelial barrier. Rather, using an intestinal macrophage replenishment model and in vitro differentiation studies, we demonstrate that laminin 511, together with the attached endothelium, promote monocyte differentiation to macrophages. Macrophage differentiation is associated with a change in integrin profile, permitting differentiating macrophages to distinguish between laminin 511 high and low areas and to preferentially migrate across laminin 511 low sites. These studies highlight the endothelial basement membrane as a critical site for monocyte differentiation to macrophages, which may be relevant to the differentiation of other cells at vascular niches.